Proenkephalin for early post–MI risk stratification: comparative prognostic performance versus NT‑proBNP and GRACE - Mathur, Ashutosh; Jha, Sumit K.; Singhal, Saurabh; Jain, Dhruv; Shahi, Harsha (International Journal of Research in Medical Sciences, 2026)
Background: Accurate post–myocardial infarction (MI) risk stratification is essential, yet clinical scores and natriuretic peptides incompletely capture early cardiorenal stress. Proenkephalin (PENK), a stable endogenous opioid precursor, reflects early glomerular dysfunction and neurohormonal activation. This study evaluated PENK for mortality prediction after MI compared with NT-proBNP and the GRACE risk score and identified optimal cutoffs. Methods: In this prospective observational cohort, 50 consecutive MI patients enrolled between December 2024 and July 2025 at a tertiary center were studied. Clinical variables, lifestyle factors, comorbidities, hemodynamics, Killip class, MI type and biomarkers (Troponin-I, serum creatinine, NT-proBNP and Proenkephalin) were measured at presentation and Day 28. GRACE scores were calculated at baseline. The primary outcome was all-cause mortality. Cox proportional hazards models assessed independent prognostic value and ROC analysis compared discrimination and derived cutoffs. Results: Mean age was 62.25±15.19 years; 68% were male, 66% smokers, 46% diabetics and 48% hypertensive. STEMI constituted 62%. Killip class I–IV: 42%, 28%, 8% and 22%. Troponin-I declined from 5,925±11,262 to 784±1,431 pg/ml (p=0.005). NT-proBNP remained elevated (4,019±4,096 to 3,880±3,695 pg/ml, p=0.001). PENK decreased from 138±35 to 89.7±28.5 pg/ml (p=0.003). Mean GRACE score was 133.6±38.1, mortality was 6%. PENK (HR 1.004, p=0.011), NT-proBNP (HR 1.001, p=0.048) and GRACE (HR 1.015, p=0.002) independently predicted mortality. ROC AUCs were 0.78 (PENK), 0.74 (NT-proBNP) and 0.69 (GRACE). Conclusions: Proenkephalin provided the strongest mortality discrimination after MI with high negative predictive value, complementing NT-proBNP and GRACE for refined post-MI risk stratification.